Beban Kerja dan Stres Kerja Perawat di Masa Pandemi Covid-19 - Padila Padila; Juli Andri (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to analyze the relationship between workload and work stress on nurses during the Covid-19 pandemic. This type of research is quantitative observational research with a descriptive method. The research sample was nurses in the inpatient room, totaling 31 people. The results showed that the most respondents in the high workload category were 19 respondents (61.3%), and in the high-stress level category were 16 respondents (51.6%) and a p-value of 0.029 (<0.05), so it can be concluded that there is the relationship between workload and nurse work stress with a positive correlation coefficient value. In conclusion, there is a significant relationship between workload and nurse work stress during the Covid-19 pandemic. Keywords: Workload, Work Stress, Nurse